Air-stable PbS quantum dots synthesized with slow reaction kinetics via a PbBr2 precursor. Issue 84 (16th September 2015) - Yuan, Lin; Patterson, Robert; Cao, Wenkai; Zhang, Zewen; Zhang, Zhilong; Stride, John A.; Reece, Peter; Conibeer, Gavin; Huang, Shujuan
<x xml:space="preserve">Abstract</x> High resolution of EDX image shows the bromine located on same position of PbS quantum dot.